Frame, value, and (in)visibility: Vik Muniz's Deslocamentos and the political economy of images. Issue 5 (20th October 2022) - Barros A., César
Abstract : This article analyses the 1995 series Deslocamentos [Displacements] by Brazilian visual artist Vik Muniz. In this work, the artist presents several photographs of press images that appear to show nothing at all. Here, Muniz prints empty squares and rectangles, adds captions and then manipulates them in order to give a sensation of 'wear and tear.' The article proposes that by 'blocking' the image's content, and by emulating the way the media presents visual material, Deslocamentos underscores the emptying of the image's value through specific forms of framing. By presenting this series of 'empty images, ' Deslocamentos invites the spectator to think of how images appear or are distributed in regimes of visibility. The article puts forward the concept of the political economy of images as a framework to think of Muniz's gesture and, more generally, the ways in which images accrue value in any given space of visibility. Images are reproducible, itinerant, entities, and given their contemporary profusion and the accelerated pace with which they circulate, any analysis of them should articulate singularity and difference to seriality and repetition. The concept of the political economy of images is provided to think through this articulation and to underscore the inextricable relation between frame, singularity, repetition and value.